Cardiac complications and failure to rescue after injury in a mature state trauma system: Towards identifying opportunities for improvement. Issue 5 (May 2020) - Scantling, Dane; Hatchimonji, Justin; Kaufman, Elinore J; Xiong, Aria; Yang, Peter; Christie, Jason D; Reilly, Patrick M; Holena, Daniel N
Highlights: Failure to rescue is an important topic in trauma but its application is different from that of elective general surgery. Cardiac complications are uncommon in trauma populations but contribute disproportionately to failure to rescue. High and low performing centers for failure to rescue from cardiac complications can be identified using a state database. This work presents an opportunity to uncover institutional factors underlying failure to rescue and improve care. Abstract: Introduction: Cardiac complications (CC) after injury are rare but contribute disproportionately to mortality. Variability in rates of CC and failure to rescue (FTR) after CC (FTR-C) within trauma systems may suggest opportunities for improvement, but we have not yet demonstrated the ability to identify high and low performers. We examined center-level rates of CC and FTR-C in a mature trauma system with the hypothesis that high-performing centers for each of these outcomes could be identified. Methods: Using a statewide trauma registry from 2007–2015, we developed multivariable logistic regression models on CC and FTR-C including patient demographics, physiology, comorbidity, and injury data. Predicted probabilities of each outcome were summed to generate expected event rates, which were compared to observed event rates to generate centerlevel observed-to-expected (O:E) ratios. We measured internal consistency between CC and FTR-C for centers using Cronbach's alpha. Results: Cardiac complications occurred in 5, 079/278, 042 (1.8%; center-level range: 0.9–3.8%) of included patients (median age 55 (IQR 34–76), 84% Caucasian, 60% male, 92% blunt, median ISS 9 (IQR5-16)). Death after CC occurred in 982/5, 097 patients for an FTR-C rate of 19.3% (center-level range: 7.8–30.4%). 10/27 centers were high-performers (95% confidence interval for O:E ratio <1) for CC and 2/27 centers were high-performers for FTR-C, but internal consistency between these metrics was poor (alpha = 0.31). Conclusion: Rates of CC and FTR-C vary significantly between hospitals in mature trauma systems but high-performing centers can be identified. Inconsistent performance between metrics suggests unknown institutional factors underlie performance for CC and FTR.